O comitê de educação do campo do Espírito Santo: sujeito coletivo de direito constituído na práxis - Ferreira, Maria Geovana Melim (2023)
The thesis defended in this research has as its theme the experience of the Countryside Education Committee of Espírito Santo (Comeces) in which we seek to investigate: What challenges, contradictions and actions of resistance have involved Comeces in the struggles to defend and strengthen the Countryside Education in Espírito Santo in the past 14 years? It aimed to analyze the actions that were taken within the scope of the struggles in the face of the challenges and contradictions that emerged in the process of consolidating Comeces, highlighting the possibilities of strengthening the professional development of the countryside working class. The theoretical contribution that supports this research dialogues with the thoughts of Florestan Fernandes, Paulo Freire, in connection with Popular Education and Rural Education, with Roseli Caldart and Derli Casali, among others. The methodological option for the Systematization of Experiences as a research methodology in the field of Popular Education in dialogue with Alfredo Guiso, Raul Mejía and Oscar Jara, made it possible to systematize the Committee's praxis, based on its dimensions of action, from the perspective of Breno Bringel´s militant research. It included the participation of representatives of social, popular and union movements and civil society, who are part of the Committee. The empirical basis involved the analysis of documents produced by Comeces, logbook record, data collected in the questionnaire and in the conversation circle. The results indicate that Comeces constitutes a collective legal entity and, as a space that forms and induces politics, in promoting concrete actions of intervention in the transformation of the reality that has been producing throughout its existence, actions of resistance to the closure processes of schools, exerting pressure on public segments to guarantee and enforce rights, which place him at the level of an organic collective intellectual of peasants, taking Gramsci as an inspiration. It calls attention, from its contradictions, the production of knowledge and indicators about the reality of the countryside education in ES, which constitute references for policy formulation and strengthen the communities' educational processes.